Of Locke’s Presence - Turkka, Tapani (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This article is about Locke’s presence in politics. In this context the prevailing understanding is that the heyday of Locke’s presence is dated to the turn of 1670s and 1680s. This interpretation was launched by Peter Laslett in 1960 in the “Introduction” to his critical edition of Locke’s Two Treatises. Today this understanding directs scholars’ efforts in Locke studies; it is a major component of the prevailing Locke-paradigm. Because of this, challenges to the Laslettian understanding merit especial attention. To this effect is e.g. Mark Knights’s recent paper (2011) in which his objective is to contribute to the development of an alternative understanding of Locke’s presence in politics. This article critically reviews Knights’s study. I ask in what sense his contribution is a challenge to the Laslettian paradigm. It will be argued that Knights’s proposition is paradoxical, and as such opens us a perspective to further Locke studies.